An assessment on the effectiveness of parliamentary control over delegated legislation in Tanzania: a case study of parliamentary committee on subsidiary legislation - Mtui, Elihaika Henry (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirement for award of the Degree of Master of Laws, (LLM) - of Mzumbe University.